Politics without a past : the absence of history in post-communist nationalism - Cohen, Shari J., 1962- (E-Duke books scholarly collection., 1999)
Argues that the rise to power of quasi-nationalist demagogues in many post-communist countries is the result of "organized forgetting" orchestrated by communist regimes that left these countries with little common history